Games to support disruptive technology adoption: the MUST Game use case - Francesca de Rosa; Christopher Strode (Serious Games Society, 2022)
Serious games can be used as a means to explore complex systems and uncertainty related challenges, therefore they may have the potential of supporting the adoption of innovative and disruptive technologies. In this paper we present the use case of the Maritime Unmanned Systems Trust (MUST) Game, which goal is to capture beliefs, attitude and perspectives of the participants with respect to the employment of maritime unmanned systems (MUS) in the maritime domain. This novel game aims at better understanding the relation between trust factors and MUS. Moreover, it explores how players make decisions with respect to MUS deployments in an increasing threat scenario. This allows to capture important information on the trade-offs related to MUS use that have an impact on maritime missions planning activities (e.g., endurance, logistics, maintenance, cost, number of assets, security and type of assets). This paper describes the game and an analysis of the outcomes of its deployment. The results show how the MUST Game design has been effective in eliciting constructive discussion around the use of MUS in maritime missions, as well as in the collection of assessments and decisions, which are currently being used in algorithmic development.